BUDAYA PERUSAHAAN DAN KINERJA KARYAWAN TRANSPORTASI UDARA - Lira Agusinta; Cecep Pahrudin; Wildan Wildan (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2017)
This study examines the influence of corporate culture on the performance of airline employees in Jakarta. These four dimensions of Hofstede culture as a means of measuring performance use airline employees in Jakarta as respondents. This research is integrates the influence of Hofstede cultural dimension on performance. The results showed that Hofstede cultural dimension has a direct positive effect on performance.